An overview of publications of the Tutorial Education Program related to High School activities (Research, Society and Development, 2021)
Objective: To map and better understand the types of interactions that exist between the activities developed by the PET groups and High School. Methodology: This is a bibliographical research, carried out from the searches of the descriptors “Tutorial Education Program or Tutorial Education”; "Tutorial Education and High School Program" and "Tutorial Education and High School" in the databases: Capes, Scielo, Academic Google and Brazilian Digital Library of Theses and Dissertations, published from January 2015 to March 2020 Results and discussion: 24 publications were analyzed. Where it was possible to identify multidisciplinary and disciplinary activities. The latter were related to Biology, Chemistry, Physics, Mathematics, History and Portuguese. No specific activities were identified in the subjects of Geography, Arts, Physical Education, Sociology, Philosophy and English. However, it was possible to identify some of these in multidisciplinary activities (Arts and Sociology). The activities took place in the 1st, 2nd and 3rd year classes. Different types of activities aimed at reading, interpreting, discussing and constructing texts were identified; lectures and debates on different relevant topics; practical activities and workshops in different areas of study; constructions, competitions and contests for materials designed by students; school support; movie theater; dissemination of undergraduate courses; among other specific courses offered. Final Considerations: The model consolidated by the PET groups is a possibility of adopting and partnering with activities that interact with High School, thinking about improving the quality of basic education, continuing studies and professional preparation.